2021
DOI: 10.1002/14651858.cd007694.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Regular treatment with formoterol and an inhaled corticosteroid versus regular treatment with salmeterol and an inhaled corticosteroid for chronic asthma: serious adverse events

Abstract: Regular treatment with formoterol and an inhaled corticosteroid versus regular treatment with salmeterol and an inhaled corticosteroid for chronic asthma: serious adverse events (Review) Copyright © 2011 The Cochrane Collaboration. Published by John Wiley & Sons, Ltd. . i Regular treatment with formoterol and an inhaled corticosteroid versus regular treatment with salmeterol and an inhaled corticosteroid for chronic asthma: serious adverse events (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“… 49 50 In the case of salmeterol, although not explicitly approved as a MART regimen, the adverse effect profiles were comparable to those of formoterol when co-administered with ICS. 51 Recent evidence indicates that even in patients who use beta-agonists judiciously, adverse events can arise if they are not accompanied by ICS. 52 This underscores the fundamental rationale against recommending stand-alone beta-agonist use in patients with asthma and provides significant support for the evolving guidelines in this domain.…”
Section: Adverse Effects From Using Beta-agonistsmentioning
confidence: 99%
“… 49 50 In the case of salmeterol, although not explicitly approved as a MART regimen, the adverse effect profiles were comparable to those of formoterol when co-administered with ICS. 51 Recent evidence indicates that even in patients who use beta-agonists judiciously, adverse events can arise if they are not accompanied by ICS. 52 This underscores the fundamental rationale against recommending stand-alone beta-agonist use in patients with asthma and provides significant support for the evolving guidelines in this domain.…”
Section: Adverse Effects From Using Beta-agonistsmentioning
confidence: 99%
“…Safety concerns related to the regular use of LABA alone have been previously reported [29]. A Cochrane review by O'Shea et al [30] recently investigated the risks of mortality and nonfatal serious adverse events related to the regular use of formoterol-ICS and salmeterol-ICS in asthma therapy: the two retrieved studies conducted in children showed no evidence of safety issues. Further evidence is needed in the paediatric population on this topic and will probably also come from ongoing paediatric studies with the combination of an ICS and formoterol for both maintenance and quick relief therapy [21].…”
Section: Key Pointsmentioning
confidence: 99%
“…The regular use of LABA alone has been associated to safety concerns in the past [ 25 ]. A Cochrane review carried out by O'Shea et al [ 26 ] has recently assessed the risk of mortality and nonfatal but serious adverse reactions associated with regular use of salmeterol-ICS and formoterol-ICS in asthma treatment. No data regarding safety problems emerged from the two retrieved studies conducted among the pediatric population, although further research in this area remains necessary.…”
Section: Focus On Recent Advances In Mild Asthma Treatmentmentioning
confidence: 99%